Role of RBC’s alloimmunization in multiple transfused thalassaemia patients - Patel, Amita Sagar; Gamit, Sejal; Gohil, Mayuri (International Journal of Research in Medical Sciences, 2016)
Background: Appropriate and regular red cell transfusion remains the main treatment of choice for a large number of patients with multiple transfusions. This study has been carried out to assess the prevalence of and to provide frequency and distribution patterns of various types of irregular red cell alloantibodies in thalassaemia major patients. Methods: 50 patients of thalassemia major were studied. The saline method, Albumin method, indirect coombs’ and Three cell panel test used for detection of red blood cell alloantibody. The variables studied were rate of red cell alloimmunization, type and specificity of RBCs alloantibodies and factors contributes to development of RBCs alloimmunization like age, gender, age at start of transfusion, number of packed cell received and ethnicity. Results: Out 50 patients of thalassemia major, 4 patients (8%) developed red cell alloantibodies respectively. The red cell alloantibodies were against Rh, Kidd, Kell, Duffy, Lewis, MNS and P system. Results of this study (P value >0.05) indicate low frequency of RBCs alloimmunization. Conclusions: Low alloimmunization rate implies that there is homogeneity of red cell antigens in blood donors & recipients. RBCs alloantibody formation was not influenced by gender, age at start of transfusions and number of packed cells received. Already alloimmunized patients get benefits from leucodepleted packed cells. Specific recommendation given on routine pre-transfusion antibody screening to ensure safer transfusion.